Ovaidan Ultrasound Image Enhancement By Pseudocolouring. - Saidin, Nafiza; Ngah, Umi Kalthum; Mashor, Mohd Yusoff (2004)
Image processing may be employed on ovarian ultrasound images to assist doctors in diagnostic analysis. The gray levels of ovarian images are usually concentrated at the zero end of the spectrum ,making the image too low in contrast and too dark for the naked eye. This paper examines the effectiveness in displaying gray level ultrasound images as colour images and proposes a pseudocolouring approach for enhancing features in ultrasound ovarian image, which allows easy discrimination Of texture information.